2020
DOI: 10.1016/j.jhazmat.2019.121778
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphate and hydrogen peroxide on the performance of a biological activated carbon filter for enhanced biofiltration

Abstract: Biofilm formation on biofilters can influence their hydraulic performance, thereby leading to head loss and an increase in energy use and costs for water utilities. The effects of a range of factors, including hydrogen peroxide and phosphate, on the performance of biological activated carbon (BAC) and biofilm formation were investigated using laboratory-scale columns. Head loss, total carbohydrates, and proteins were reduced in the nutrient-enhanced, oxidant-enhanced, and nutrient + oxidant-enhanced BAC filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In this study, biofilms obtained from phosphate treatment samples showed less total cells (Figure 2) and restricted/limited development on coupon surfaces when they were observed by SEM (Figure 3). Contrary to these results, other studies in drinking water related systems, reported an increase of cells in biofilms developed under different phosphate treatments (Fang et al, 2009;Noh et al, 2019). An explanation for these contradictory results might be that these studies were performed using annular bioreactors (Fang et al, 2009) and biological FIGURE 7 | Heatmap with the relative abundance of annotated genes in the whole metagenome of each of the sequenced samples.…”
Section: Effect Of Phosphate Treatment On Biofilm Structurementioning
confidence: 78%
See 2 more Smart Citations
“…In this study, biofilms obtained from phosphate treatment samples showed less total cells (Figure 2) and restricted/limited development on coupon surfaces when they were observed by SEM (Figure 3). Contrary to these results, other studies in drinking water related systems, reported an increase of cells in biofilms developed under different phosphate treatments (Fang et al, 2009;Noh et al, 2019). An explanation for these contradictory results might be that these studies were performed using annular bioreactors (Fang et al, 2009) and biological FIGURE 7 | Heatmap with the relative abundance of annotated genes in the whole metagenome of each of the sequenced samples.…”
Section: Effect Of Phosphate Treatment On Biofilm Structurementioning
confidence: 78%
“…activated carbon columns (Noh et al, 2019) where biofilms were less exposed to hydraulic forces than under representative hydraulic conditions in DWDS. Besides, previous studies have shown that the addition of phosphate in drinking water can reduce the synthesis of EPS by biofilms (Fang et al, 2009;Kirisits et al, 2013;Liu et al, 2016;Noh et al, 2019).…”
Section: Effect Of Phosphate Treatment On Biofilm Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that increasing PO 4 3− levels in drinking water reduces the production of EPS in biofilms 22,46,47 . Among other functions, EPS is involved in protecting biofilm cells from external damage as well as maintaining its integrity and aiding the attachment of cells to substrates 48 .…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 is an indispensable chemical in daily life. It has many applications in fields such as biology ( Chang et al, 2021 ; Noh et al, 2020 ; Guarino et al, 2019 ), medicine ( Andersen et al, 2006 ; Kozlova et al, 2015 ; Wang Y. et al, 2020 ), chemical industry ( Chung et al, 2020 ; Zhang et al, 2021 ), environmental protection ( Dinakar et al, 2020 ; Moreno, 2011 ). As a clean oxidant, the decomposition of H 2 O 2 only yields H 2 O, which does not pose an environmental risk.…”
Section: Introductionmentioning
confidence: 99%